2011
DOI: 10.1254/jphs.11r05cr
|View full text |Cite
|
Sign up to set email alerts
|

Glycoprotein 130 Cytokine Signal as a Therapeutic Target Against Cardiovascular Diseases

Abstract: Abstract. Postnatal cardiomyocytes have only limited capacity of proliferation. Therefore, the myocardium is intrinsically equipped with cardioprotective machineries and protects itself from pathological stresses. One of the most important cardioprotective systems is the signal network of autocrine/paracrine factors, including neurohumoral factors, growth factors, and cytokines. In this review, we focus on the roles of interleukin-6 (IL-6) family cytokines, also known as glycoprotein 130 (gp130) cytokines, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 75 publications
0
36
0
Order By: Relevance
“…Therefore, site-specific PEGylation is an innovative application to increase the potency and half-life of IL-11 (by more than 10-fold to ϳ300 -500 min in rats; unpublished data). After IL-11 binds to the IL-11 receptor, the ligand-receptor complex interacts with a common receptor subunit, glycoprotein 130 (gp130), leading to gp130-associated kinase-mediated tyrosine phosphorylation (11). The cytoprotective mechanisms of IL-11 leading to reductions in necrosis, inflammation, and apoptosis have been investigated in other cell types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, site-specific PEGylation is an innovative application to increase the potency and half-life of IL-11 (by more than 10-fold to ϳ300 -500 min in rats; unpublished data). After IL-11 binds to the IL-11 receptor, the ligand-receptor complex interacts with a common receptor subunit, glycoprotein 130 (gp130), leading to gp130-associated kinase-mediated tyrosine phosphorylation (11). The cytoprotective mechanisms of IL-11 leading to reductions in necrosis, inflammation, and apoptosis have been investigated in other cell types.…”
Section: Discussionmentioning
confidence: 99%
“…The cytoprotective mechanisms of IL-11 leading to reductions in necrosis, inflammation, and apoptosis have been investigated in other cell types. In cardiomyocytes, IL-11 reduces injury and fibrosis by JAK-STAT3 (Janus kinase-signal transducer and activator of transducer 3) pathway activation (11,26,40). In vascular endothelial and intestinal epithelial cells, IL-11 protects against oxidant-induced necrosis and apoptosis via mechanisms involving ERK MAPK, Akt (protein kinase B), and/or induction of heat shock protein 25 (39,44,61).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these cardioprotective signaling pathways are believed to be therapeutic targets against cardiovascular diseases (5). However, unexpectedly, recent studies have proposed that signaling molecules may exhibit differential functions depending on their kinetics.…”
Section: New and Noteworthymentioning
confidence: 99%
“…The mechanism underlying this effect may be attributed to the stimulation of STAT3 activated by IL-11. As described previously (13), cardiac myocytes release large quantities of IL-6 family cytokines, including IL-11, in conditions of pathological stress. These cytokines activate a common signaling pathway, the JAK/STAT pathway, through their unique receptor system.…”
Section: Discussionmentioning
confidence: 75%
“…We therefore suspect that our results were also attributed to a different pathway existing upstream of apoptosis. It has been shown that STAT3 not only influences the apoptotic pathway but also reduces reactive oxygen species (ROS); the JAK/ STAT3 pathway upregulates the transcription of manganese superoxide dismutase and metallothionein, both of which are known ROS scavengers (13). ROS act as mediators for post-ischemic myocardial stunning, and studies have shown that reperfusion of the ischemic hearts with ROS scavengers improves functional recovery and reduces the occurrence of IR-induced arrhythmias (18).…”
Section: Discussionmentioning
confidence: 99%